2010
DOI: 10.1007/s10096-010-0978-z
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphism of the C-reactive protein (CRP) gene and a deep infection focus determine maximal serum CRP level in Staphylococcus aureus bacteremia

Abstract: C-reactive protein (CRP) is widely used in early detection of sepsis or organ dysfunction. Several single nucleotide polymorphisms (SNPs) in the CRP gene are shown to be associated with variability of basal CRP. To clarify the effect of these SNPs to CRP response in systemic infections, we compared genetic and clinical data on patients with Staphylococcus aureus bacteremia (SAB). Six SNPs in the CRP gene region (rs2794521, rs30912449, rs1800947, rs1130864, rs1205 and rs3093075) were genotyped in 145 patients a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 40 publications
2
9
1
Order By: Relevance
“…Our data is in agreement with a recent study which focused on deep infections, where CRP-286 (C>T>A) polymorphism is found to be significantly associated with maximal CRP levels during the first week of infection [46]. Interestingly, this same triallelic CRP-286 (C>T>A) polymorphism, which we found to be associated with maximal CRP levels in S. aureus bacteraemia, has been related to high basal CRP levels as well [14,46-49]. The triallelic SNP association with CRP level strongly supports recent work described above and represents a reproducible association between genetic variation and this biomarker of high interest.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our data is in agreement with a recent study which focused on deep infections, where CRP-286 (C>T>A) polymorphism is found to be significantly associated with maximal CRP levels during the first week of infection [46]. Interestingly, this same triallelic CRP-286 (C>T>A) polymorphism, which we found to be associated with maximal CRP levels in S. aureus bacteraemia, has been related to high basal CRP levels as well [14,46-49]. The triallelic SNP association with CRP level strongly supports recent work described above and represents a reproducible association between genetic variation and this biomarker of high interest.…”
Section: Discussionsupporting
confidence: 93%
“…This result mirrors a previous study which found a similar relationship between higher frequencies of A-allele carriers and higher concentration of serum CRP levels [14]. Our data is in agreement with a recent study which focused on deep infections, where CRP-286 (C>T>A) polymorphism is found to be significantly associated with maximal CRP levels during the first week of infection [46]. Interestingly, this same triallelic CRP-286 (C>T>A) polymorphism, which we found to be associated with maximal CRP levels in S. aureus bacteraemia, has been related to high basal CRP levels as well [14,46-49].…”
Section: Discussionsupporting
confidence: 93%
“…CRP has been recognized as a good marker of systemic inflammation and a valuable clinical tool in severe infections [ 18 ], but clear cut-off levels to guide clinical decisions in SAB have not been demonstrated. The maximal CRP level might not be useful because it is influenced by genetic variation in the genes responsible for CRP synthesis [ 19 ]. This study was undertaken to assess CRP concentrations at various time points during SAB infection that would enable to identify patients with complications.…”
Section: Introductionmentioning
confidence: 99%
“…Potentially important clinical characteristics particularly the details of antibiotic therapy, the role and timing of surgery, sepsis severity and presence of in hospital complications were not well captured in the database or incorporated into the model. The impacts of liver disease and CRP polymorphisms [22][23][24][25][26] were beyond the scope of the study and could not be accounted for in the model. Such limitations impact both the performance of the model at a population level (particularly over longer time periods) and its ability to control for significant covariates when defining the relationship between CRP and key outcomes.…”
Section: Time (H)mentioning
confidence: 98%